Pengembangan Potensi Wisata Sumaru Endo Kabupaten Minahasa: Analisis Daya Tarik, Aksesibilitas, dan Kunjungan Wisatawan - Lantu, Dela Natalia; Lobja, Xaverius Erick; Andaria, Kalvin Salindeho (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2023)
The research aims to determine how to develop attractiveness, accessibility, facilities, infrastructure, promotion, and increase tourist visits. Research methods with qualitative descriptive methods. Data collection by interviews, observation, and documentation. The results showed that the tourist attraction of Sumaru Endo is the panorama of Lake Tondano. The potential that can be developed is hot springs and water tourism and lodging. Some facilities and infrastructure have been damaged and reduced security. The existence of tourist attractions can add to the economy of the community. The accessibility of tourist attractions is quite good but constrained by the absence of public transportation. Tourism promotion has not been fully carried out optimally. It is necessary to develop tourism services and tourist attractions so that tourist activities are more varied. How to increase visits is done by reducing entrance ticket prices, improving facilities and infrastructure, and promotions.